Aplikasi Android Pengenalan Kebudayaan Daerah Kepulauan Bangka Belitung - Ellyta, Dea; Josi, Ahmat; Setya Pratama, Muhammad (Jurnal Inovasi Teknologi Terapan, 2024)
Regional arts and culture constitute a sector with tremendous potential for development and preservation. Each region boasts its own unique cultural characteristics, thus necessitating a widespread introduction to these cultural facets. Particularly, the cultural heritage of the Bangka Belitung Islands showcases distinctive and captivating artistry and traditions. However, these cultural elements often remain insufficiently recognized on a broader scale. One of the reasons behind the waning interest of the younger generation in the cultural heritage of the Bangka Belitung Province is the lack of control from the local government, allowing an influx of foreign cultures. Therefore, this research aims to develop an Android-based application that introduces the arts and cultural heritage of the Bangka Belitung Islands. The application development employs the Scrum software development methodology using the Kotlin programming language. The primary objective of this project is to familiarize and facilitate users in discovering information about the arts and cultural heritage of the Bangka Belitung Islands. This research is conducted in collaboration with the Department of Tourism, Culture, Sports, and Youth of the Bangka Belitung Islands Province. The blackbox testing yielded highly satisfactory validation results, while the user acceptance testing produced a percentage of 87.8%, indicating its suitability for use.